Penggunaan Story Akun Instagram @Dapoer.Delapansebagai Digital Marketing pada Generasi Z di Masa Pandemi Covid-19 - Kuncoroyakti, Yohanes Arie; Wiklestari, Indah; Syahda, Tiara; Prisilia, Iftitah Chika (LUGAS Jurnal Komunikasi, 2022)
The development of advanced technology invites many positives that have many uses that many of its users can utilize, one of the Instagram users who utilize the Feature owned by Instagram which is the founder of small businesses. Social media Instagram has many of its users one of which is generation Z.  Generation Z is a group of people born in 1996 - 2010, Generation Z grew together with the internet and social media. Instagram also makes it easier for small business founders to promote the goods they sell, one account that utilizes it is, account @dapoer.delapan. Owner acoount @dapoer.delapan uses digital marketing as a form of marketing that utilizes digital technology. Digital marketing is also defined as marketing activity using internet-based media (Wardhana, 2015). This study aims to analyze the advantages and disadvantages of using Story Instagram as digital marketing on account @dapoer.delapan, which uses a qualitative approach with a phenomenological approach. The subject of this study is the owner of the Instagram @dapoer.delapan account, where the object of this study is the story Instagram that has a variety of supporting features as a digital marketing medium. The results of this study conclude that although there are many ease and advantages that can be felt to Z generation as home-grown small business operators. But it also has shortcomings to pay particular attention to if it wants its business to grow as well as profit and gain time-saving efficiency